THE PROJECT PLAN WRITING WHICH RELATED TO 20 YEARS RAJABHAT UNIVERSITY STRATEGIES, ACCORDING TO 4 MISSIONS OF PHRANAKHON RAJABHAT UNIVERSITY - อ้อยแดง งามพิศ (Academic Journal Phranakhon Rajabhat University, 2020)
This research aimed to 1) study the relation of project plan of Faculty of Humanities and Social Sciences with 20 years Rajabhat University strategies, according to 4 missions of Phranakhon Rajabhat University and 2) the guidelines of writing project plan which related to 20 years Rajabhat University strategies, according to 4 missions of Phranakhon Rajabhat University. This research was qualitative and the research instrument was interview form which was in-depth interview. The key-informer were 1) Dean of Faculty of Humanities and Social Sciences, 2) Vice Dean for Management and Planning, 3) the chairperson of 17 curriculums; 1 from each, and 4) 20 officers who were writing project plan for Faculty of Humanities and Social Sciences, Phranakhon Rajabhat University. The data was analyzed by summarizing and interpreting the study points. The research results showed that 1) the relation of project plan of Faculty of Humanities and Social Sciences with 20 years Rajabhat University strategies, according to 4 missions of Phranakhon Rajabhat University were 4 strategies as 1) local development found that supporting and building self-awareness of taking advantage by using area in community, support students in learning to develop wisdom and community products to enable students having sustainable in career development. 2) Teacher production and development found that supporting and building characteristic to students according to Sufficiency Economic Philosophy to students to make them understand and adherence in working correctly, success in their career, smart and self-sufficiency. 3) The education development found that learning and teaching integration, and support students in working skills with community leaders and local leaders and can work with local government organization effectively. And 4) management development found that there was potential improvement of management according to missions efficiency and having officers development in every levels to have potential, supporting equipments, learning equipments to be enough and efficiency. And 2) the guideline of writing project plan which related to 20 years Rajabhat University strategies, according to 4 missions of Phranakhon Rajabhat University found that the project planing writing of Faculty of Humanities and Social Sciences must set objectives related to university strategies indicators correctly, clearly, must check, controlling, and follow up working processes and evaluate the project to reach the project goals.